Property Tax Diagnostic Manual - Roy, Kelly; White, Roland; Anand, Aanchal (World Bank, Washington, DC, 2020)
The Property Tax Diagnostic Manual (hereafter "Manual") provides guidance on how to analyzeand assess immovable property tax systems, diagnose the strengths and weaknesses of such systems, and develop a property tax intervention strategy where needed. Its higher objective is to support increasingly fair and stable tax systems in low- and middle-income countries, with significant potential for sustainable improvements in achieving key revenue, equity, and efficiency objectives. This Manual focuses specifically on the recurrent, immovable property tax. It does not address other land-based property taxes such as property transfer taxes, capital gains taxes, and one event property revenues (land sales, leases) or personal taxes on movable property such as boats, airplanes, and motor vehicles. Although these other property taxes are not directly addressed, successful reforms for the recurrent, immovable property tax must take intoaccount the interactions that exist between the immovable property tax and these other formsof property taxation. The Manual is primarily designed to assist practitioners from governments, development partners, and civil society practitioners to identify, analyze, and develop potential property tax reforms. The Manual lays out an analytical approach that can help identify property tax performance potential, challenges and opportunities, evaluate remedial property tax policyand administrative reform measures, and design a strategic action plan to implement those recommended interventions. A conceptual framework for the property tax, its policy and administration components, and reform strategy options are provided along with numerous examples of international experience.